Flexicurity - an open method of coordination, at the national level? - Barbier, Jean-Claude; Colomb, Fabrice; Madsen, Per Kongshøj (Paris, 2009)
"Flexicurity, as a notion, has spread since 2000, from its use in Netherlands and Denemark. The origin of the word is well known : invented by a sociologist who was an aide to the Dutch minister of labour in 1990. Demark became emblematic of flexicurity in 2004-2005. We compare public and social debates in Denmark and in France during from 2000 to 2008 : we show that the same superficial international discourse was used by both countries but with different goals and within different institutions. International discourses are not a signal of convergence of social systems and labour markets. We could rather say taht common ideas expressed in English are adapted and translated in order to fit the national system so that they can be used as resources by actors in the elaboration of national compromises. From that point of view, "Europeanization" is confined to a superficial layer of political discourses and to their justification at a very abstract and general level."